Early detection of cystic fibrosis lung disease: multiple-breath washout versus raised volume tests. Issue 4 (22nd November 2006) - Lum, Sooky; Gustafsson, Per; Ljungberg, Henrik; Hülskamp, Georg; Bush, Andrew; Carr, Siobhán B; Castle, Rosemary; Hoo, Ah-fong; Price, John; Ranganathan, Sarath; Stroobant, John; Wade, Angie; et al.
Abstract : Background: Lung clearance index (LCI), a measure of ventilation inhomogeneity derived from the multiple-breath inert gas washout (MBW) technique, has been shown to detect abnormal lung function more readily than spirometry in preschool children with cystic fibrosis, but whether this holds true during infancy is unknown. Objectives: To compare the extent to which parameters derived from the MBW and the raised lung volume rapid thoraco–abdominal compression (RVRTC) techniques identify diminished airway function in infants with cystic fibrosis when compared with healthy controls. Methods: Measurements were performed during quiet sleep, with the tidal breathing MBW technique being performed before the forced expiratory manoeuvres. Results: Measurements were obtained in 39 infants with cystic fibrosis (mean (SD) age 41.4 (22.0) weeks) and 21 controls (37.0 (15.1) weeks). Infants with cystic fibrosis had a significantly higher respiratory rate (38 (10) vs 32 (5) bpm) and LCI (8.4 (1.5) vs 7.2 (0.3)), and significantly lower values for all forced expiratory flow-volume parameters compared with controls. Girls with cystic fibrosis had significantly lower forced expiratory volume (FEV0.5 and FEF25–75 ) than boys (mean (95% CI girls–boys): –1.2 (–2.1 to −0.3) for FEV0.5 Z score; FEF25–75 : –1.2 (–2.2 to −0.15)). When using both the MBW and RVRTC techniques, abnormalities were detected in 72% of the infants with cystic fibrosis, with abnormalities detected in 41% using both techniques and a further 15% by each of the two tests performed. Conclusions: These findings support the view that inflammatory and/or structural changes in the airways of children with cystic fibrosis start early in life, and have important implications regarding early detection and interventions. Monitoring of early lung disease and functional status in infants and young children with cystic fibrosis may be enhanced by using both MBW and the RVRTC.